THE CHALLENGES OF MICE INDUSTRY AFTER COVID-19 IN MYANMAR - Phu, May Me (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Since the outbreak of the covid-19 has started globally, there are a lot of disruptions in tourism business. Travel, tourism, hotel and MICE industry are facing immense challenges at present. Especially Myanmar is the developing country and business growth is still growing. Epidemic causes hundreds of events cancelled all over the world, and wakening to news of cancellations or postponements. MICE industry required to reconsider the options and to balance the priorities of upholding the health and safety of staff, sponsors, and attendees which is necessary to meet financial obligations and minimizing the losses caused by disruption. This research is a qualitative study and the purpose of the study is study the challenges of the MICE business that will need to face during the recovery process. The aim of the study is to point out what is affecting the MICE industry during the crisis and what will be awaiting future for the MICE travel to step forward like other travel. In-depth interview is conducted with 9 managers of the hotels and DMCs from both of the destinations Yangon and Mandalay for investigation and analysis the role of each in the MICE industry. The thematic analysis method is used in this research to analysis the data. The study finds out that it is important to survive the situation with no revenue and the effective recovery plan. After the crisis, the collaborative strategies will be supportive for the future tourism industry in Myanmar. The study points out how the issue of social distancing impacting on the MICE products. This study will be helpful for MICE business crucial need to encourage tourism operators to involve with crisis preparedness and disaster-management strategies and it is important to increase a better understanding of the consumer response to disastrous event by all components of the value chain.